In vitro investigation of pollen growth of pear (p. comminus l.) and apple (m. sylvestrismiller) plants exposed to heat stress - Gur, Nazmi; Yolacti, Semiha; Topdemir, Aykut (Parlar Scientific Publications, 2020)
The study aims to determine how the pollens of pear {Primus comminis L.) and apple {Malus sylvestris Miller) plants are affected by high and low temperatures and to reveal the negative effects of climate change on the yield of various fruit-bearing plants. In all plants, the following were used as pollen germination temperatures: 5°C, 10°C, 15°C, 20°C, 25°C, 30°C and 35°C. A temperature of 22°C ± 1°C was used for the control group. After 3 hours of germination, the samples were removed from the incubator and fixed using 10% ethanol added to the culture medium placed on slides. Measurements were performed using an ocular micrometre. The effects of temperature, which is an important stress factor for plants, on pollen germination and pollen tube growth of pear and apple plants were investigated. The temperature at which the germination rate and pollen tube length were least affected was 25°C, which was the closest temperature to the control group {22°C ± 1°C). Each plant was affected by low and high temperatures at different rates. © by PSP.
Keywords: Heat stress; Malus sylvestris Miller; Pollen germination; Pollen tube elongation; Prunus comminis L.